Priority Queue Algorithm Enhances Public Report Handling Efficiency and Accountability: Algoritma Priority Queue Meningkatkan Efisiensi dan Akuntabilitas Penanganan Laporan Publik - Detuage, Rivni; Santa, Kristofel; Moningkey, Efraim R. S. (Universitas Muhammadiyah Sidoarjo, 2026)
The mechanism for handling public aspirations and reports in the Minahasa Regency Regional People's Representative Council (DPRD) still faces inefficiency and low accountability due to the manual process. The conventional First-In-First-Out (FIFO) system is unable to differentiate the urgency of reports, resulting in delayed follow-up of critical reports. This study designs and implements a web based Public Information Portal (PIP) that integrates a priority queue algorithm to automatically sort reports based on their urgency. The development method used is the Waterfall method. Test reults sgow significant performance improvements, marked by a recuation in waiting time for high priority reports by more than 50% and increased accuracy of handling based on urgency levels. This system also strengthens public accountability thorugh a real time status tracking feature. By offering a technical solution not found in previous research—namely an automatic prioritization mechanism specifically for managing aspirations within the DPRD—this study fills a research gap and makes a significant contribution to improving service quality and fulfilling the mandate of the Public Information Disclosure Law. Highlights• Priority queue mechanism reduces waiting time for high-priority reports by over 50%.• Automatic urgency-based sorting improves accuracy and responsiveness in report handling.• Real-time status tracking increases public accountability and transparency. KeywordsPublic Information Portal; Priority Queue Algorithm; Regional People's Representative Council; E-Government Transparency; Public Service Efficiency